The Zunyi conference and the rise of Mao Zedong - Kampen, Thomas (Internationales Asien-Forum, 1986)
This article examines Mao Zedong's rise to leadership of the Chinese Communist Party between 1934 when he had lost all his former power and 1945 when he had become the undisputed leader of the CCP. The most crucial turning-point in his career was the Zunyi Conference of January 1935. Recent Chinese publications have contradicted most Western research about this period; fifty years later it is now possible for the first time to provide a detailed description of this conference and its background. In contrast to earlier assumptions Mao Zedong did not become official or unofficial Party leader during the Long March, but had to fight for nearly a decade until he became chairman of the Central Committee of the CCP in 1945.